2016
DOI: 10.1038/srep35022
|View full text |Cite
|
Sign up to set email alerts
|

Stoichiometry patterns in the androdioecious Acer tegmentosum

Abstract: This study evaluates stoichiometry patterns in the androdioecious Acer tegmentosum, a species characterized by a rare reproductive system where males and hermaphrodites coexist. Altogether 31 hermaphrodites and 29 male plants were harvested and samples of leaves, current-year shoots, branches and coarse roots were analyzed to explore gender differences in biomass, C, N and P concentrations of these four components. The nitrogen to phosphorus relationship of each component was examined using SMA estimates. Male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…We used standardized major axis regression (SMA; sma function within smatr R package) to test for significant differences between watering treatments in biomass allocation to different components. SMA is a procedure for assessing heterogeneity of regression slopes which characterizes the best fit bivariate line between two variables (Warton, Duursma, Falster, & Taskinen, ; Zhang et al, ). The data set used for this study is publicly available (Drake, Vårhammar, et al, ) and the analysis code to reproduce all the results, including the figures and tables, is available at https://bitbucket.org/Kumarathunge/great-drought.…”
Section: Methodsmentioning
confidence: 99%
“…We used standardized major axis regression (SMA; sma function within smatr R package) to test for significant differences between watering treatments in biomass allocation to different components. SMA is a procedure for assessing heterogeneity of regression slopes which characterizes the best fit bivariate line between two variables (Warton, Duursma, Falster, & Taskinen, ; Zhang et al, ). The data set used for this study is publicly available (Drake, Vårhammar, et al, ) and the analysis code to reproduce all the results, including the figures and tables, is available at https://bitbucket.org/Kumarathunge/great-drought.…”
Section: Methodsmentioning
confidence: 99%
“…An experiment in Populus cathayana also showed that males had lower N:P ratios than females under equally P‐deficient treatments (Zhang et al, 2014). Likewise, a study regarding the androdioecious plant, Acer tegmentosum , revealed that the scaling slope for foliar P vs. N was steeper in males than in hermaphrodites (Zhang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%